The Influence of Financial Technology on Profitability in Jordanian Commercial Banks - Baker Akram Falah Jarah; Mohammad Yousef Alghadi; Murad Ali Ahmad Al-Zaqeba; Mohamed Ibrahim Mugableh; Belal Zaqaibeh (conscientia beam, 2024)
Indexed by Scopus